Community Risk Assessment: Spatial Patterns and GIS-Based Model for Fire Risk Assessment - A Case Study of Chiang Mai Municipality - Srivanit, Manat (Journal of Architectural/Planning Research and Studies (JARS), 2018)
The main purpose of this study is to develop a GIS-based approach to fire risk assessment to identify sites for disaster mitigation planning and management. Fire risk assessment has two main factors: the vulnerability and capacity for mitigation of the areas, as well as the areas with a fire history. The selection of risk factors is mainly based on stakeholder analysis, involving four groups: urban planners, fire wardens, local residents and local government officials. The above data are integrated into raster-based GIS software and then spatial analysis is performed using an overlay technique to generate the fire risk, ranging from high to low according to its sensitivity to fire or fire-inducing capability. The result is a map of the varying levels of fire risk across the city. The weight to each factor is determined by an Analytical Hierarchy Process (AHP). This model is illustrated with a case study of fire risk of area in the Chiang Mai Municipality (CMM). It is suggested that risk mapping is helpful for fire management to minimize fire hazards.